Modelling and Experimental Analysis of Noise Transmission through Wall of a Railway Vehicle - Peter Zvolensky; Juraj Grencik; Lubomir Kasiar; Peter Volna; Riccardo Licciardello (Communications - Scientific letters of the University of Zilina, 2017)
The paper presents results of a grant research project dealing with acoustic properties of the walls and floor of a railway passenger coach investigated by means of the experimental analysis of noise produced during train runs and corresponding simulations. In the research, conditions and theoretical approaches for possible reconstructions of walls and floor of the railway passenger coach using new fibrous-microstructure acoustic materials were defined, with the aim of increasing the sound reduction index. The properties of the proposed materials were compared in terms of the acoustic energy transfer through the porous microstructure calculated by means of simulations. The final acoustic effects of different solutions for the incorporation of the materials in the floor structure and in the complete body of the rail passenger coach were evaluated. In this paper the effects on interior noise of the introduction of a new material for floor and wall are presented.